The Impact of the CPTPP on International Trade in ASEAN Countries - Sermcheep, Sineenat; Ariyasajjakorn, Danupon (Asian Journal of Applied Economics, 2026)
Background and Objectives: The Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) is widely regarded as one of the most ambitious “high standard” trade agreements currently in force, combining deep tariff liberalization with wide-ranging provisions related to services, investment, regulatory coherence, and emerging areas such as the digital economy. For the Association of Southeast Asian Nations (ASEAN), the CPTPP presents both opportunities and challenges because ASEAN economies are highly trade dependent, deeply embedded in regional value chains, and already connected through multiple overlapping free trade agreements—most notably the Regional Comprehensive Economic Partnership (RCEP). While four ASEAN members (Brunei Darussalam, Malaysia, Singapore, and Viet Nam) are already CPTPP parties, several large ASEAN economies remain outside the agreement. This uneven participation raises a key policy question: will CPTPP-related gains remain concentrated among existing ASEAN participants, or could broader ASEAN accession generate more inclusive benefits at the regional level? Moreover, expanded CPTPP membership—particularly the potential accession of major economies such as China—may reshape patterns of comparative advantage and alter the balance between trade creation and trade diversion for ASEAN economies. Against this background, the study aims to assess how different CPTPP membership configurations may affect ASEAN economies’ trade performance and macroeconomic outcomes. Specifically, it evaluates the distribution of impacts across ASEAN members and non-members under alternative accession scenarios, with attention to changes in trade flows, income (GDP), terms of trade, and welfare. Methodology: The study employs a computable general equilibrium (CGE) approach using the Global Trade Analysis Project (GTAP) framework and database to simulate the economy-wide impacts of CPTPP-related trade liberalization. The GTAP model is well suited to this task because it captures interlinkages among production sectors and countries through a consistent global input–output structure, allowing the analysis to trace how trade policy shocks affect production, consumption, trade patterns, factor allocation, and welfare. The simulation design considers four scenarios: (1) the current CPTPP configuration (including the United Kingdom’s accession) as the baseline liberalization setting; (2) an expanded CPTPP that adds applicants (China, Taiwan, Ecuador, Costa Rica, Uruguay, and Ukraine); (3) scenario (2) plus Thailand’s accession; and (4) a hypothetical full ASEAN accession in which all ASEAN-10 members join the CPTPP. To provide an upper-bound benchmark for long-run effects, the simulations assume full tariff elimination among participants and incorporate only those non-tariff measure (NTM) reductions that are quantifiable within the GTAP database constraints. Countries/regions and sectors in the GTAP database are aggregated into analytically relevant groupings for ASEAN members and partner blocs, and into a smaller set of production sectors to facilitate interpretation of macro and sectoral channels. Key Findings: The simulation results indicate that ASEAN economies already participating in the CPTPP tend to experience gains in GDP and welfare under the current membership configuration, whereas most non-member ASEAN economies face adverse effects, consistent with trade diversion away from non-members. When additional economies apply to join the CPTPP—particularly large and diversified producers—impacts become more heterogeneous across ASEAN. The entry of a major economy such as China is associated with more adverse outcomes for several ASEAN countries, reflecting intensified competition and shifts in comparative advantage within the enlarged bloc. When Thailand is included as a CPTPP member, macroeconomic outcomes improve markedly for Thailand relative to non-membership, and broader ASEAN participation tends to mitigate some adverse effects faced by non-members. Under the hypothetical scenario of full ASEAN accession, several ASEAN economies show stronger improvements in macro indicators such as GDP, welfare, and terms of trade, suggesting that wider ASEAN participation can reduce intra-regional exclusion costs and support regional trade performance. However, the magnitude of gains does not increase proportionally as more ASEAN members join. Instead, benefits may diminish for early joiners in some cases, implying that the expansion of membership can redistribute gains within ASEAN and reduce the relative advantage of early participants. Sectoral results further indicate that ASEAN economies’ gains are closely tied to the ability to strengthen comparative advantage in specific industries and to position effectively within regional production networks. Policy Implications: The findings suggest that, on balance, CPTPP participation is preferable for ASEAN economies, particularly for those currently outside the agreement, because exclusion may entail measurable opportunity costs through trade diversion and reduced welfare. At the same time, the results highlight that ASEAN-wide gains depend on strategic adaptation. To maximize benefits, ASEAN members should identify sectors with the strongest potential for comparative advantage and reinforce competitiveness through industrial upgrading, productivity enhancement, and value-chain development. Given the evidence that membership expansion can dilute relative advantages, policy coordination at the ASEAN level is also important: strengthening regional production networks, harmonizing standards, and improving trade facilitation can help ASEAN economies share gains more broadly and sustain competitiveness within a larger CPTPP environment. Finally, because CGE results reflect modeled long-run comparative-static adjustments and only partial NTM coverage, complementary work that examines sensitive sectors, realistic tariff phase-in schedules, and dynamic channels (e.g., investment and technology diffusion) would further strengthen policy guidance.